Re-thinking children׳s agency in extreme hardship: Zimbabwean children׳s draw-and-write about their HIV-affected peers. (January 2015) - Campbell, Catherine; Andersen, Louise; Mutsikiwa, Alice; Madanhire, Claudius; Skovdal, Morten; Nyamukapa, Constance; Gregson, Simon
Abstract: We compare two analyses of the same 'draw-and-write' exercises in which 128 Zimbabwean children represented their HIV-affected peers. The first, informed by the 'New Social Studies of Childhood', easily identified examples of independent reflection and action by children. The second, informed by Sen׳s understandings of agency, drew attention to the negative consequences of many of the choices available to children, and the contextual limits on outcomes children themselves would value: the support of caring adults, adequate food, and opportunities to advance their health and safety. Conceptualisations of agency need to take greater account of children׳s own accounts of outcomes they value, rather than identifying agency in any form of independent reflection and action per se.